Abnormal functional connectivity of the amygdala is associated with depression in Parkinson's disease. Issue 2 (27th December 2014) - Hu, Xiao; Song, Xiaopeng; Yuan, Yonggui; Li, Erfeng; Liu, Jiajia; Liu, Weiguo; Liu, Yijun; Stacy (Chair), Mark; Lang, Anthony; Napier, Celeste; Samuel, Michael; Strafella, Antonio; et al.
ABSTRACT Depressive symptoms are common in Parkinson's disease (PD), but the pathophysiology and neural basis underlying depression in PD is not well understood. Abnormal functional connectivity of the amygdala with various cortical and subcortical areas has been observed in major depressive disorder, indicating that dysfunction of the corticolimbic network may be involved in the pathogenesis of major depressive disorder. However, little is known about alterations of amygdala functional connectivity in depressed PD patients. In the present study, 20 depressed PD patients, 40 nondepressed PD patients, and 43 matched healthy controls underwent neuropsychological tests and resting‐state functional MRI scanning. Between‐group differences in amygdala functional connectivity network were examined using t tests. Compared to the nondepressed PD patients, depressed PD patients showed increased left amygdala functional connectivity with the bilateral mediodorsal thalamus, right amygdala functional connectivity with the left superior temporal gyrus, and left calcarine gyrus. Compared to the healthy controls, the depressed PD group also showed increased left amygdala functional connectivity with the bilateral mediodorsal thalamus, but decreased left amygdala functional connectivity with the left putamen, left inferior frontal gyrus, and the right cerebellum, as well as decreased right amygdala functional connectivity with the left inferior orbitofrontal gyrus, the left gyrus rectus, and the right putamen. The increased connectivity between limbic regions and decreased connectivity between the corticolimbic networks may reflect impaired high‐order cortical regulatory effects on the emotion‐related limbic areas, which may lead to mood dysregulation. Our study should advance the understanding of neural mechanisms underlying depression in PD. © 2014 International Parkinson and Movement Disorder Society